2022
DOI: 10.3390/ijms232112781
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Attenuates the Effects of Peripheral Inflammation in a Human In Vitro Blood–Brain Barrier Model

Abstract: Biological mediators secreted during peripheral chronic inflammation reach the bloodstream and may damage the blood–brain barrier (BBB), triggering central nervous system (CNS) disorders. Full-fledged human BBB models are efficient tools to investigate pharmacological pathways and mechanisms of injury at the BBB. We here employed a human in vitro BBB model to investigate the effects of either plasma from inflammatory bowel disease (IBD) patients or tumor necrosis factor α (TNFα), a cytokine commonly released i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The RNA-seq analysis revealed increases in IFITM3 expression in bEnd.3 cells co-cultured with LPS-activated Raw264.7 cells but such increases were not found at protein levels by western blot analysis ( Fig 4E and 4F ). Cytokines/chemokines and other secreted molecules during systemic inflammation may impair the BBB integrity [ 55 ]. At the BBB, the most abundant tight junction protein is claudin-5 that is involved in progression of neurodegenerative disorders including AD [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-seq analysis revealed increases in IFITM3 expression in bEnd.3 cells co-cultured with LPS-activated Raw264.7 cells but such increases were not found at protein levels by western blot analysis ( Fig 4E and 4F ). Cytokines/chemokines and other secreted molecules during systemic inflammation may impair the BBB integrity [ 55 ]. At the BBB, the most abundant tight junction protein is claudin-5 that is involved in progression of neurodegenerative disorders including AD [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Catorce and Gevorkian [ 63 ] reviewed LPS-induced murine neuroinflammation models and suggested that peripherally induced inflammation by LPS may trigger neuroinflammation leading to Aβ and/or tau pathology, neurodegeneration and cognitive impairment. Considering increased BBB permeability by LPS [ 55 , 65 ] and fibrinogen infiltration via a leaky BBB [ 85 ], we investigated the BBB permeability by immunofluorescence microscopy using antibodies specific to fibrinogen and CD31, a marker for endothelial cells. We found that fibrinogen fluorescence signals were increased and exclusively limited to the areas positive for CD31 fluorescence signals in LPS-treated mice ( Fig 6 ), indicating that LPS treatment did not induce infiltration of fibrinogen into the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone attenuates inflammation, 29 while both T2DM 30 and fatty liver disease 31 are associated with increased levels of inflammatory markers. Hence, the beneficial effects of pioglitazone on both diabetes and SLD may be the result of an attenuation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…When ready, HBP were rinsed once with warm DMEM/HG/0.1% BSA and then incubated in DMEM/HG/0.1% BSA supplemented or not with 5 or 10 ng/mL of TNFα. These concentrations were selected based on previous in vitro studies published by us and others [ 64 , 65 , 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%